Cover Image. (25th October 2022) - Unknown
Abstract : Phylogenetic trees and their relationship to singular‐value decomposition clusters (outside), for homeodomains (left) and Ras GTPases (right). The top trees are clustered based on sequence similarity. The bottom trees are clustered based on taxonomy; major clades (metazoa, fungi, etc.) are shaded. For details, please see: Baxter‐Koenigs et al. 2022, Protein Science, https://doi.org/10.1002/pro.4422